Comparison of MOOC Platforms in India - Dafauti, Balam; Mythili, G (International Journal of Educational Communications and Technology, 2023)
Massive open online courses (MOOCs) are the most current and significant innovation in higher education. MOOCs (massive open online courses) are increasingly popular, with huge enrolment numbers. The MOOC projects launched by India include NPTEL, ePG Pathshala, NROER, IITBombayX, and SWAYAM. There are several online platforms that provide access to online courses in order to encourage continuous education. The present study examines the potential of Massive Open Online Courses (MOOCs) in the educational environment. It is difficult to adopt MOOCs in India for various reasons. Due to the advent of SWAYAM, some of these problems have already been solved. In this paper, we will describe MOOCs, as well as the institutions and universities that offer them, and provide a basic comparison between the multiple MOOC platforms. This study conducted an observational assessment of four MOOC sites in India and identified important factor for comparison. Each of the twelve identified parameters represents the usefulness of the MOOC platforms. The final result is to determine the most effective MOOC platform in Indian Context.